The Impact of Brexit on Levels of Corporate Credit Risk: Evidence from UK and EU Non-financial Companies - Výstupová,Veronika; Almahrouq,Haidar (2019)
The impact of the UK’s decision to leave the EU has received a lot of attention in scientific research in recent years. The effect of Brexit on many different variables and factors related to financial markets and general economy has been studied extensively. Corporate credit risk is, however, an area which did not receive as much attention. This study therefore focuses on the quantification of the impact of Brexit-related events on the levels of corporate credit risk in the UK and the EU, respectively. Using the structural Merton model, monthly real-world default probabilities are estimated and used in a regression analysis, together with other PD determinants in order to assess the effects of Brexit. The results of our empirical analysis indicate that, following the announcement of the referendum, default probabilities increased both for the UK and the EU companies. In contradiction to the previous studies, however, the effect of referendum result announcement was associated with a decrease in default probabilities for the European companies and insignificant results for the UK companies. All aforementioned effects can be regarded as marginal.
Keywords: Brexit; credit risk; probability of default; Merton model; panel data analysis